(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Remote learning, also described as distance education or online learning, has experienced rapid increase in resent decade, predominantly driven by technological improvement and the Covid-19 pandemic (Anderson, 2021). As a new learning method, it allows students to gain knowledge outside of the standard classroom environment using the latest digital tools and platforms. Especially, when compared traditional education, it is somehow challenging, however, it has a numerous opportunities.